A review of interoperability and possibilities for data analysis from virtual world environments. (18th July 2012) - Lorenzo, Carlos-Miguel
Massively multi-user online virtual environments are gaining widespread attention and use. There are both proprietary and open-source implementations of these environments and they also use different communication protocols and data formats. After studying some of those protocols and formats, this paper provides a review of the current state of the art in the interoperability of these systems and elaborates on the possibilities of data analysis provided by them. A set of features regarding interoperability and data analysis is proposed, including the use of open communication protocols and content formats, then some of the most popular virtual world platforms (Second Life, OpenSim, Taiga, Active Worlds, Open Wonderland, Croquet Project, Tundra and Sirikata) are compared in terms of those features.